Potential patient harms from misinterpretation of publically reported surgical outcomes. (22nd May 2018) - Sathianathen, Niranjan J.; Albersheim‐Carter, Jacob; Labine, Lucas; Watson, Brett; Konety, Badrinath R.; Weight, Christopher J.
Abstract : Objective: To determine how the general public interprets surgical complication rates presented from a publicly available online surgical‐rating website. Subjects and Methods: An in‐person electronic survey was administered at the local State Fair to a convenience sample. Participants were presented with a representative output from an online surgeon‐rating website and were asked to choose from three statistically equivalent surgeons for a hypothetical medical decision. We then suggested that their insurance company would only cover one surgeon and probed their willingness to pay to switch surgeons for a small chance of lowering the risk of a complication (0.7%, 95% confidence interval [CI] −8.1% to 9.5%, P = 0.9). We quantified the characteristics of those willing to switch, the degree of misinterpretation, and the subsequent potential patient harms. Results: There were 343 completed responses. When presented with a hypothetical healthcare decision, most participants ( n = 209, 61%) said they were willing to pay out‐of‐pocket expenses to switch to a statistically equivalent surgeon. Those who were willing to pay to switch surgeons were more likely to be older (odds ratio [OR] 1.02, 95% CI 1.01–1.03), poorer (OR 1.81, 95% CI 1.07–3.11), previously had cancer (OR 5.9, 95% CI 1.9–25), and misinterpreted the data (OR 3.03, 95% CI 1.87–4.96). Those who were willing to pay out‐of‐pocket expenses were more inaccurate in their estimation of surgeon complication rates (mean estimate 34.0% vs 8.9%, P < 0.001, correct rate = 3.6%), and on average were willing to pay $6 494 (95% CI 4 108–8 880). Conclusion: Understanding of a publicly reported surgical‐complication website is often prone to misinterpretation by the general population and may lead to patient harm from a financial aspect.